Establishing an Online Community of Practice for Robotics Educators - Santos, Daniel Moreira Dos; Oliveira, Márcia Gonçalves De (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
This paper aims to present and analyze the development of an Online Community of Practice (CoP) composed of teachers who graduated from a hybrid Educational Robotics (ER) course in the state of Espírito Santo, Brazil. The CoP was established to foster deeper engagement with technological and methodological studies, as well as to design and share investigative and problem-solving pedagogical practices involving robotics. This initiative is part of the Educational Product developed within an ongoing Professional Doctorate research project, which adopts action research as its methodological framework. The study enabled the identification of the group's stage of development and an in-depth analysis of its formation process. The findings indicate that the CoP is an effective approach to continuing teacher education in ER, as it promotes collaborative learning, allows for flexible engagement with study topics, and supports the creation of a collectively validated repertoire of teaching practices.